Involvement of a Gene Encoding Putative Acetate Kinase in Magnetosome Synthesis in Magnetospirillum magneticum AMB-1 - ARIS TRI WAHYUDI (HAYATI Journal of Biosciences, 2006)
A nonmagnetic mutant of Magnetospirillum magneticum AMB-1, designated NMA40, was constructed by mini-Tn5 transposon mutagenesis to identify genes involved in magnetosome synthesis. Transposon delivery was carried out through conjugation between M. magneticum AMB-1 as a recipient and Escherichia coli S17-1 (λ pir) carrying pUTmini-Tn5Km1 as a donor strain. NAM40 did not respond to the magnetic fields and completely lacked of magnetosome in the cell. DNA sequence/gen interrupted by transposon (called flanking DNA) was isolated by inverse PCR and cloned into pGEM-T Easy. Alignment of the DNA sequence of the flanking DNA allowed the isolation of an open reading frame (ORF2) within an operon consisting of three genes. The amino acid sequence deduced from ORF2 showed homology with acetate kinase from Sinorhizobium meliloti (50% identity and 67% similarity), which function for acetate metabolism. Further analysis revealed that upstream of ORF2 is ORF1, had homology with phosphotransacetylase of S. meliloti (67% identity, 77% similarity), and ORF3 located downstream of ORF2, had homology with hypothetical protein of Thermotoga maritima (30% identity, 60% similarity). ORF2 was subsequently isolated, cloned, and overexpressed in Escherichia coli BL21 (DE3) pLysS as an ORF2-Histag fusion polypeptide. Key words: Magnetospirillum magneticum AMB-1, magnetosome synthesis, transposon mutagenesis, cloning, overexpression